Chronic Kidney Disease Increases Risk of Incident HFrEF Following Percutaneous Coronary Intervention - Lai, Wenguang; Zhao, Xiaoli; Yu, Sijia; Mai, Ziling; Zhou, Yang; Huang, Zhidong; Li, Qiang; Huang, Haozhang; Li, Huanqiang; Wei, Haiyan; Guo, Dachuan; Xie, Yun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Chronic kidney disease (CKD) is very common in patients who are at a high risk of developing incident heart failure with reduced ejection fraction (HFrEF). However, the harmful effect of CKD on incident HFrEF has not yet been examined among patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI). Methods Patients undergoing PCI with baseline left ventricular ejection fraction (LVEF) ≥ 40% were included from January 2007 to December 2018 (ClinicalTrials.gov NCT04407936). We defined incident HFrEF as a follow-up LVEF of <40% within 3–12 months after discharge. Multivariable logistical regression was performed to examine the association of CKD with incident HFrEF. Results Overall, of 2,356 patients (mean age 62.4 ± 10.7 years, 22.2% women), 435 (18.5%) had CKD, and 83 (3.5%) developed incident HFrEF following PCI. The rate of incident HFrEF in the CKD group was higher than that in the non-CKD group (6.9 vs. 2.8%; p < 0.001). Multivariate logistic regression analysis indicated that CKD was an independent risk factor of incident HFrEF [adjusted odds ratio (aOR) = 1.75; 95% CI, 1.03–2.92; p = 0.035] after adjustment for confounders including age, gender, diabetes, hypertension, atrial fibrillation, congestive heart failure (CHF), baseline LVEF, ACEI/ARB, and statins. Furthermore, patients with incident HFrEF have a higher ratio of all-cause mortality compared to those without HFrEF (26.5 vs. 8.1%; p < 0.001). Conclusions Our results suggested that CKD was associated with increased risk of incident HFrEF, which was related to higher all-cause mortality in patients with CAD undergoing PCI. On this basis, more aggressive measures should be taken to prevent patients with CKD undergoing PCI from developing HFrEF.